Prenatal and infant antibiotic exposure and childhood growth, obesity and cardiovascular risk factors: The Rhea mother–child cohort study, Crete, Greece. Issue 1 (9th August 2021) - Margetaki, Katerina; Stratakis, Nikos; Roumeliotaki, Theano; Karachaliou, Marianna; Alexaki, Maria; Kogevinas, Manolis; Chatzi, Leda; Vafeiadi, Marina
Summary: Background: Early‐life antibiotic use has been hypothesized to promote weight gain and increase the risk of childhood obesity. Objectives: To examine the associations of prenatal and infant antibiotics with childhood growth, adiposity and cardiometabolic traits in the Greek Rhea cohort. Methods: We used data from 747 mother–child pairs with anthropometric measurements drawn from medical records or measured at 4 and 6 years of age. Antibiotic exposure was assessed by maternal report during pregnancy and at the first year of life. Children were classified as exposed to antibiotics prenatally if the mother received at least one course of oral antibiotics during pregnancy and postnatally if the mother reported that the child received at least one oral antibiotic treatment during the first year of life. Outcomes included repeated weight, body mass index (BMI), waist circumference, body fat (%), total cholesterol and blood pressure. We applied mixed effects, linear and log‐binomial regression models after adjusting for important covariates. Results: Around 14.6% of the participating children were prenatally exposed to antibiotics and 32.4% received antibiotics during the first year of life. Prenatal exposure to antibiotics was associated with a twofold increase in the risk for obesity (risk ratio [RR]; 95% confidence interval [CI]: 2.09 [1.58, 2.76]) and abdominal obesity (RR [95% CI]: 2.56 [1.89, 3.47]) at 6 years. Postnatal exposure to antibiotics was associated with increased weight (beta [95% CI]: 00.25 [0.06, 0.44]) and BMI (beta [95% CI]: 0.23 [0.003, 0.45]) SD scores from 2 to 7 years of life. Conclusion: Early‐life antibiotic use was associated with accelerated childhood growth and higher adiposity.